Skill components of higher education in the era of sustainable development: an analytical study among university students in Qatar - Alshawi, Ali A. Hadi; Ali, Abdel-Samad M.; Raïq, Hicham (Frontiers in Education, 2023)
The current study investigates the status of education for sustainable development (ESD) as an approach applied to higher education. The study undertakes cognitive learning, behavioral learning, and socio-emotional learning as the three dimensions of ESD. It examines to what extent curricula and educational structures currently applied by Qatar University contribute to sustainable development skills from students' attitudes. Data were collected from 319 students. Factor analysis was conducted to regroup skill items within consistent dimensions of 16 core skills. A multivariate logistic regression analysis was undertaken to examine the relationship between the core skills and five sustainable development skills. The study introduces new reclassified core skills based on students’ real experience. Five logistic regression models were explored. Model 1 finds two predictors that only increase the Odds of innovative thinking skills. Model 2 shows five predictors that increase the Odds of critical thinking skills. Model 3 defines three predictors that increase the Odds of resolving problems skills. Model 4 mentions four predictors that increase the Odds of communication/coordination skills. Model 5 shows two predictors that increase the Odds of decision-making skills. Such findings may help target specific skills and bring significant changes to the outcomes of higher education.